Crime victims’ rights in the European area of justice and Polish legislation - Banach-Gutierrez, Joanna Beata (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In recent years, more and more attention has been focused on the interests of crime victims, including their enlarging role in criminal proceedings. The procedural rights of, and assistance to, victims of crime are gradually becoming essential aspects of contemporary criminal justice systems. In the transnational context at the European Union level, the Directive 2012/29/EU establishing minimum standards on the rights, support and protection of victims of crime is of significant importance as this legal instrument contains some concrete rights for victims of crime and clearer obligations imposed on the competent national authorities. Unfortunately, in many EU Member States the regulations on the standing victims in criminal proceedings are not properly or fully implemented into national legislation. This paper aims to give some insight to the provisions of the EU Victims’ Directive, and also the issue regarding its transposition into the Polish legal order.
Keywords: prawa ofiar przestępstw; wymiar sprawiedliwości w sprawach karnych UE; prawa człowieka w sprawach karnych